Application of FT-IR spectroscopy and chemometric technique for the identification of three different parts of Camellia nitidissima and discrimination of its authenticated product - Tew, Wan Yin; Ying, Chen; Wujun, Zhang; Baocai, Liu; Yoon, Tiem Leong; Yam, Mun Fei; Jingying, Chen (Frontiers in Pharmacology, 2022)
Camellia nitidissima is a golden camellia recognised in Chinese herbology and widely used as a tea and essential oils in Chinese communities. Due to the broad range of pharmacological actions, it can be a useful drug in treating a variety of diseases. However, unethical sellers adulterated the flower with other parts of Camellia nitidissima in their product. This study used an integrated tri-step infrared spectroscopy and chemometric approach to discriminate flowers, leaves, and seeds of C. nitidissima. The three different parts of C. nitidissima were well distinguished using Fourier transform infrared spectroscopy (FT-IR), Second derivative infrared spectra (SD-IR), and two-dimensional correlation infrared spectra (2D-IR). The FT-IR and SD-IR spectrum of the samples were subjected to principal component analysis (PCA), PCA-class, and Orthogonal Partial Least Square Discriminant Analysis (OPLS-DA) for classification and discrimination studies. The three parts of C. nitidissima were well separated and discriminated by PCA and OPLS-DA. The PCA-class model's sensitivity, accuracy, and specificity were >94%, indicating that PCA-class is a good model. Additionally, the RMSEE, RMSEP, and RMSECV values for the OPLS-DA model were low, and the sensitivity, accuracy, and specificity were all 100%, indicating that the created model is good. Furthermore, both PCA-class and OPLS-DA score 18/20 and 17/20 for discriminating adulterated and other TCM reference flower samples from C. nitidissima, respectively. Consequently, it was demonstrated that by combining an infrared spectroscopic method with a chemometric approach, it is possible to differentiate distinct portions of C. nitidissima and discriminate adulterated samples from C. nitidissima flower.